EVALUATING USER SATISFACTION AND EFFICIENCY OF E-REPORT SYSTEMS IN VOCATIONAL SCHOOLS: A PIECES FRAMEWORK ANALYSIS FROM TEACHER PERSPECTIVES - Vhivi Bulan (Universitas Citra Bangsa, 2024)
This study aims to evaluate the user satisfaction and efficiency of E-Rapor system by qualitative approach with PIECES framework on SMK Negeri 1 Kupang. The study focuses on uncovering the ice in the E-Rapor system. The research aims to identify strengths and areas for improvement in the system. Findings indicate that while the E-Rapor system significantly streamlines the process of student assessment and reporting, some performance issues, such as system slowdowns during peak usage, require optimization. Teachers typically feel that the system is easy to use, processes data quickly and is accurate. Nonetheless, changes in report structures and improvements in data protection such as the deployment of tougher encryptions or regular audits are needed. It is further recommend that technological support services be refined to serve user needs more effectively. The study findings suggest that while the system has had an overall positive effect on student learning, further revisions will be necessary for consistent use and optimal user satisfaction, ultimately informing clear guidance for future improvements throughthe PIECES framework.